2016
DOI: 10.18632/oncotarget.13221
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of DNA methylation biomarkers in hepatocellular carcinoma

Abstract: DNA methylation is an epigenetic mechanism in the pathogenesis of hepatocellular carcinoma (HCC). Here, we conducted a systematic meta-analysis to evaluate the contribution of DNA methylation to the risk of HCC. A total of 2109 publications were initially retrieved from PubMed, Web of Science, Cochrane Library, Embase, CNKI and Wanfang literature database. After a four-step filtration, we harvested 144 case-control articles in the meta-analysis. Our results revealed that 24 genes (carcinoma tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
58
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(69 citation statements)
references
References 33 publications
4
58
0
7
Order By: Relevance
“…Increased methylation of the promoter region of the MGMT gene has been reported in hepatocellular carcinoma. 45 In the present study, two DMRs were identified in the body of the MGMT gene, one of which was hypomethylated and the other was hypermethylated. The expression of MGMT was downregulated in the livers of patients with advanced NAFLD.…”
Section: Tss200supporting
confidence: 47%
“…Increased methylation of the promoter region of the MGMT gene has been reported in hepatocellular carcinoma. 45 In the present study, two DMRs were identified in the body of the MGMT gene, one of which was hypomethylated and the other was hypermethylated. The expression of MGMT was downregulated in the livers of patients with advanced NAFLD.…”
Section: Tss200supporting
confidence: 47%
“…Concordance between aberrant methylations in tumor tissues and plasma is generally good, indicating that plasma could represent a tumor surrogate when tissue is not available. The field has been widely investigated and a meta-analysis of these studies has been published [20] . In the diagnostic setting, from the analysis of 150 plasma samples from patients with HCC, benign liver disease (including cirrhosis and chronic inactive hepatitis) and normal controls, Huang and co-workers found that the combined aberrant methylation of four genes (APC, GSTP1, RASSF1A and SFRP1) has a significant diagnostic value for HCC [21] , confirming the results obtained in tumor tissues [22] .…”
Section: Aberrant Methylation Of Cfdna In Plasma or Serum In Hccmentioning
confidence: 99%
“…Как подтверждают результаты многочисленных исследований, профили метилирования ц-ДНК в крови пациентов с ГК хорошо согласуются с данными по метилированию ДНК в образцах опухолевой ткани ОБЗОРНЫЕ СТАТЬИ ТОМ 5 / VOL. 5 [29]. В связи с этим поиск опухоль-специфических биомаркеров метилирования в циркулирующих опухолевых ДНК представляется перспективным направлением в диагностике и лечении ГК.…”
Section: обзорные статьиunclassified
“…По данным обширного метаанализа 144 экспериментальных статей, посвященных сравнению профилей метилирования ДНК в нормальных и опухолевых тканях печени, для тканей ГК характерно гиперметилирование промоторов генов APC, WIF1, SFRP1 и CDH1. Кроме того, гиперметилирование генов WIF1 и CDH1 часто отмечается в ц-ДНК из сыворотки крови пациентов с ГК [29].…”
Section: обзорные статьиunclassified
See 1 more Smart Citation